Ferroelectrics and Their Applications 2018
DOI: 10.5772/intechopen.77388
|View full text |Cite
|
Sign up to set email alerts
|

BaTiO3-Based Lead-Free Electroceramics with Their Ferroelectric and Piezoelectric Properties Tuned by Ca2+, Sn4+ and Zr4+ Substitution Useful for Electrostrictive Device Application

Abstract: Dense microstructure BaTiO₃ (BT) ceramic with c/a ~1.0144 and average grain size ~7.8 μm is developed by achieving the ferroelectric parameters Psat. = 24.13 μC/cm 2 and Pr = 10.42 μC/cm 2 with lower coercive field of Ec = 2.047 kV/cm. For BT ceramic, the "sprout" shape nature is observed for strain-electric field measurements with remnant strain ~ 0.212%, converse piezoelectric constant ~376.35 pm/V and electrostrictive coefficient Q 33~ 0.03493 m 4 /C 2. To tune the piezoelectric properties of BT ceramic, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…This response trend is similar to energy density variation under the influencing applied electric field and is many times studied for estimating the energy holding or capacitor-material suitability of such polymer–NP composites. Figure shows the trend of the increasing current density with the increase of the applied electric field as observed in previous studies with BT crystals . The results suggest that the current density shows a stable linear response to the applied electric field, which is a key requirement for sensing purposes.…”
Section: Results and Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This response trend is similar to energy density variation under the influencing applied electric field and is many times studied for estimating the energy holding or capacitor-material suitability of such polymer–NP composites. Figure shows the trend of the increasing current density with the increase of the applied electric field as observed in previous studies with BT crystals . The results suggest that the current density shows a stable linear response to the applied electric field, which is a key requirement for sensing purposes.…”
Section: Results and Discussionsupporting
confidence: 68%
“…Figure 6 shows the trend of the increasing current density with the increase of the applied electric field as observed in previous studies with BT crystals. 32 The results suggest that the current density shows a stable linear response to the applied electric field, which is a key requirement for sensing purposes. This comparison plot in Figure 6 suggests that the polymer−NP composite sample having more NPs can transfer the applied energy to BT NPs more efficiently or vice versa.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…Several studies have shown that a fine domain structure of barium titanate (BT) material during the synthesis routes can greatly improve its dielectric and piezoelectric properties. For BT at room temperature, d 33 values ranging from 350 [ 36 ] to 500 pC/N and d 31 = −185 pC/N were achieved [ 34 ]. Thus, PZT d 33 piezoelectric coefficient varies from 152 to 593 pC/N [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several research projects have documented on piezoelectric, ferroelectric, dielectric, and diffused phase transition properties of barium calcium zirconate titanate (BCZT), and barium strontium titanate (BST) piezoceramics [19,151,152,[158][159][160][161][162][163][164][165][166].…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%